Customer preferences on master bedroom furniture / Nur Nazariah Md Tahir - Md Tahir, Nur Nazariah (Faculty of Applied Sciences, 2014)
Bedroom furniture basically consists of three kind of furniture that is bed, wardrobe and dresser. Over the past decades, many factors have caused these changes, including globalization of materials and technology. As in the domino effect, customer preferences on the furniture also have changed within these times. Therefore, the objective of this study is to determine customer preferences on master bedroom furniture. Lack of research and data on this study has become the cause to do this research. Questionnaires have been distributed to the selected area and the results have also been determined. The results of this study have been analyzed into three categories; income level, age and gender. From the results, there were not many differences between the factors. Collected data throughout the research can be used by related parties to enhance the industry.